"YouthTalk": positively engaging young people in Edinburgh. Issue 4 (13th June 2017) - Kilmurry, Evelyn
Abstract : Purpose: The purpose of this paper is to describe the multi-agency approach adopted in Liberton/Gilmerton, Edinburgh in Scotland to positively involve young people in shaping local service provision and to tackle rising anti-social behaviour. The approach and methodology of the engagement process used is described in detail in order to enable other authorities and services to learn from established practice. Design/methodology/approach: The approach was developed over two years and saw the expression of over 1, 500 young people's views, which influenced 40 local statutory and voluntary services to deliver on over 70 pledges locally to improve service provision in direct response to expressed need. Findings: The paper summarises the positive outcomes delivered as a result of the work which has transformed the way that partners plan, design and deliver their services locally, and has resulted in many significant outcomes including a 17 per cent drop in youth crime, young people opening their own Youth Cafe, and launching their annual YouthTalk Awards Event. The initiative has been held up by the HMIe as a model of best practice, and is being replicated across the city through other library locations as a successful way to engage young people in improving the quality of life in their communities. Practical implications: The paper includes implications for the development of library and other services to work in an integrated way to positively engage with young people in order for them to be included in decision-making processes. Originality/value: This paper contributes to the studies on best practice in working positively with young people.